Clinical and functional correlates of financially deprived women with first‐episode psychosis. Issue 3 (25th March 2018) - Hui, Christy L.M.; Ko, Wai Tung; Chang, Wing Chung; Lee, Edwin H.M.; Chan, Sherry K.W.; Chen, Eric Y.H.
Abstract : Background: Women, especially those with low‐socio‐economic status and financial deprivation, are found to be affected by mental illnesses disproportionately. We compared the clinical, functioning and cognitive characteristics between the financially deprived women with first‐episode psychosis and their non‐deprived women counterparts. Method: A cross‐sectional analysis of consecutively recruited first‐episode psychosis women patients was conducted. A total of 93 financially deprived women patients and 105 non‐deprived women patients aged 25 to 55 years were compared in terms of demographic, premorbid and help‐seeking characteristics, baseline clinical characteristics, baseline functioning and baseline cognitive functioning. Results: Financially deprived women were older ( P = .005), had received less education ( P = .001), more likely to live alone ( P < .001) and with a higher proportion of immigrants ( P = .001). Whereas there was no significant difference found in duration of untreated psychosis, deprived women had more severe depressive symptoms ( P = .021) and more severe negative symptoms, in terms of avolition‐apathy ( P = .003) and anhedonia‐asociality ( P = .008). They also perform worse in social and occupational functioning ( P = .002) and a range of cognitive abilities. Conclusions: Nearly half of the adult female patients with first‐episode psychosis in Hong Kong encountered persistent financially difficulties. The fact that they suffer from more severe symptoms and worsened functioning and cognitive abilities at an early stage of illness shows that this subgroup of patients warrant assistance and attention.